Acute sedation-associated complications in GI endoscopy (ProSed 2 Study): results from the prospective multicentre electronic registry of sedation-associated complications. Issue 3 (3rd January 2018) - Behrens, Angelika; Kreuzmayr, Anton; Manner, Hendrik; Koop, Herbert; Lorenz, Albrecht; Schaefer, Claus; Plauth, Mathais; Jetschmann, Jens-Uwe; von Tirpitz, Christian; Ewald, Marcus; Sackmann, Michael; Renner, Wanja; et al.
Abstract : Objectives: Sedation has been established for GI endoscopic procedures in most countries, but it is also associated with an added risk of complications. Reported complication rates are variable due to different study methodologies and often limited sample size. Designs: Acute sedation-associated complications were prospectively recorded in an electronic endoscopy documentation in 39 study centres between December 2011 and August 2014 (median inclusion period 24 months). The sedation regimen was decided by each study centre. Results: A total of 368 206 endoscopies was recorded; 11% without sedation. Propofol was the dominant drug used (62% only, 22.5% in combination with midazolam). Of the sedated patients, 38 (0.01%) suffered a major complication, and overall mortality was 0.005% (n=15); minor complications occurred in 0.3%. Multivariate analysis showed the following independent risk factors for all complications: American Society of Anesthesiologists class >2 (OR 2.29) and type and duration of endoscopy. Of the sedation regimens, propofol monosedation had the lowest rate (OR 0.75) compared with midazolam (reference) and combinations (OR 1.0–1.5). Compared with primary care hospitals, tertiary referral centres had higher complication rates (OR 1.61). Notably, compared with sedation by a two-person endoscopy team (endoscopist/assistant; 53.5% of all procedures), adding another person for sedation (nurse, physician) was associated with higher complication rates (ORs 1.40–4.46), probably due to higher complexity of procedures not evident in the multivariate analysis. Conclusions: This large multicentre registry study confirmed that severe acute sedation-related complications are rare during GI endoscopy with a very low mortality. The data are useful for planning risk factor-adapted sedation management to further prevent sedation-associated complications in selected patients. Trial registration number: DRKS00007768; Pre-results.